A multipathogen selective enrichment broth for simultaneous growth of Salmonella enteria, Escherichia coli O157:H7, and Shigella flexneri. Issue 1 (8th September 2017) - Suo, Yujuan; Gao, Shigang; Xie, Yanping; Liu, Yanhong; Qu, Yang; Lin, Ting; Zhou, Changyan
Abstract: Salmonella, Shigella, and Escherichia coli O157:H7 contaminate similar types of food and cause foodborne disease. The objective of this study was to develop a selective enrichment broth for simultaneous enrichment of Salmonella Enteritidis, E . coli O157:H7, and Shigella flexneri (SES) using Bile salt No. 3, potassium tellurite, novobiocin sodium, and lithium chloride as selective agents. Developed SES broth not only enriched both of the target pathogens to as high as 9 log10 CFU/ml after 24 hr incubation at 37 °C with 10–100 CFU/ml of inoculation concentration, but also could successfully support the simultaneous enrichment of target pathogens with similar growth rates and inhibit the growth of most nontarget bacteria effectively. The enrichment effect of SES was confirmed by artificial contamination test coupled with multiplex PCR. In summary, SES has been shown to be a promising multiplex selective enrichment broth for the detection of the three pathogens on a single‐assay platform. Practical applications: It is different from traditional microbiological enrichment broths used in detecting Salmonella Enteritidis, Escherichia coli O157:H7, and Shigella flexneri, which limit the application of multipathogen detection in a single‐assay format. SES can be considered as an effective multipathogen selective enrichment broth for simultaneous growth of S . Enteritidis, E. coli O157:H7, and S. flexneri, and inhibit most of other common pathogens. In addition, SES combined with multi‐PCR could be directly used for the detection of the three pathogens in meat, which solved issues of no suitable enrichment broth, ensured detection accuracy, and saved detection time and cost.